The Dominance Flow Shop Scheduling Problem - Vasquez-Perez, O (Elsevier B.V., 2018)
We introduce a new line of analysis of Flow Shop scheduling problems, for the case of two jobs and assuming that processing times are unknown. The goal is to determine the domination relations between permutation and non-permutation schedules. We analyze the structural and dominance properties that ensue in this setting, based on the critical paths of schedules. © 2018 Elsevier B.V.